Berita Hoaks vs Berita Layak: Tipologi Khalayak Media Sosial Perspektif Fikih Jurnalistik - M Musyaffa (JURNAL ILMIAH SYI'AR, 2020)
Indonesian audiences have not been able to distinguish between decent news and hoax news on social media. In the Islamic context, there is actually a rule of journalistic fiqh or social media fiqh which can become the main frame of reference to guide social media audiences (netizens) in their position as content producers as well as content consumers (prosumer). This study specifically examines the typology of audiences from a journalistic fiqh perspective. A qualitative critical approach is used as an attempt to comprehensively analyze and present data between the phenomenon of decent news and hoaxes on social media platforms with relevant literature presentations. This study found that proper news comes from the journalistic work of the mainstream mass media with the principles according to the principles of the Journalistic Code of Ethics and Journalistic Jurisprudence. Hoax news arises from the subjectivity of fans and enthusiasts, or active audiences (posters) without data and facts.